2014
DOI: 10.1158/2326-6066.cir-13-0124
|View full text |Cite
|
Sign up to set email alerts
|

Cancer–Testis Antigen Expression in Digestive Tract Carcinomas: Frequent Expression in Esophageal Squamous Cell Carcinoma and Its Precursor Lesions

Abstract: Cancer-testis (CT) antigens are attractive tumor antigens for cancer immunotherapy. They comprise a group of proteins normally expressed in germ cells and aberrantly activated in a variety of human cancers. The protein expression of eight cancer-testis antigens [MAGEA, NY-ESO-1, GAGE, MAGEC1 (CT7), MAGEC2 (CT10), CT45, SAGE1, and NXF2] was evaluated by immunohistochemistry in 61 esophageal carcinomas (40 adenocarcinoma and 21 squamous cell carcinoma), 50 gastric carcinomas (34 diffuse and 16 intestinal type), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
4
29
0
1
Order By: Relevance
“…This suggests that raising immunity to one or more of these antigens with a vaccine prior to any evidence of tumor would strengthen immunosurveillance and reduce risk, eventually replacing prophylactic mastectomies. CT antigens have also been found in squamous dysplasia leading to head and neck cancer, and squamous cell carcinoma in situ in esophageal biopsies [24,25], two other cancers that could be targeted for prevention in the premalignant stage.…”
Section: Candidate Antigens For Preventative Vaccinesmentioning
confidence: 99%
“…This suggests that raising immunity to one or more of these antigens with a vaccine prior to any evidence of tumor would strengthen immunosurveillance and reduce risk, eventually replacing prophylactic mastectomies. CT antigens have also been found in squamous dysplasia leading to head and neck cancer, and squamous cell carcinoma in situ in esophageal biopsies [24,25], two other cancers that could be targeted for prevention in the premalignant stage.…”
Section: Candidate Antigens For Preventative Vaccinesmentioning
confidence: 99%
“…A 2005 study by Liang et al measured the MAGE1 gene expression via RT-PCR and reported the gene overexpression in 25.7% of esophageal SCCs (20). The prevalence of MAGE1 in studies by Haier et al in 2006 and Chen et al in 2014 was 50% and 57% respectively (18, 19). Immunohistochemistry technique was used in these studies, similar to ours (18, 19).…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of MAGE1 in studies by Haier et al in 2006 and Chen et al in 2014 was 50% and 57% respectively (18, 19). Immunohistochemistry technique was used in these studies, similar to ours (18, 19). A 2011 study by Forghanifard et al showed that MAGE1 mRNA was overexpressed in 90.2% of esophageal SCC specimens in the Iranian population (29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many of the tumor antigens targeted by therapeutic cancer vaccines are also expressed in premalignant lesions and immune responses against them can be detected (714). In addition, all of the proposed mechanisms of action of therapeutic vaccines, such as development of tumor antigen specific cytotoxic T cells or antibodies and formation of immune memory, are the same as those that are expected of vaccines focused on reducing the risk of developing invasive cancer (1517).…”
Section: Review Of the Recommendations And Discussionmentioning
confidence: 99%